Polyaniline-poly(vinyl alcohol) IPN-composite prepared from potassium dichromate embedded PVA film: A material for humidity sensing application - Misra N.; Bharti S.; Kapusetti G.; Upadhyay D.K.; Jaiswal S.; Panda H.S.; Prakash R. (My University, 2025)
Polyaniline-polyvinyl alcohol (PANI-PVA) interpenetrating network composite film is successfully prepared by in situ polymerization of aniline within PVA film embedded with different concentrations of potassium dichromate (K 2Cr2O7). The resulted composite is characterized by UV-Visible spectroscopy, SEM and XRD, TGA techniques and confirmed the formation of interpenetrating network formation of PANI within PVA matrix. Electrical conductivity of the composite films increase from 10 -6 to 10-2 S/cm with the increase in the loading of dichromate from 10-4 to 10-2 M. Further, exposing in humidity environment, the conductivity of the composite films increases from 14 to 100% with the increase in humidity conditions from 11.3 to 84.3%. © 2011 IACS.